Molecular epidemiological tracing of a cattle rabies outbreak lasting less than a month in Rio Grande do sul in southern Brazil - Itou, Takuya; Fukayama, Toshiharu; Mochizuki, Nobuyuki; Kobayashi, Yuki; Deberaldini, Eduardo R. [UNESP]; Carvalho, Adolorata A. B. [UNESP]; Ito, Fumio H.; Sakai, Takeo (My University, 2016)
Background: Vampire bat-transmitted cattle rabies cases are typically encountered in areas where the disease is endemic. However, over the period of a month in 2009, an outbreak of cattle rabies occurred and then ended spontaneously in a small area of the Rio Grande do Sul State in southern Brazil. To investigate the epidemiological characteristics of this rabies outbreak in Rio Grande do Sul, 26 nucleotide sequences of rabies virus (RABV) genomes that were collected in this area were analyzed phylogenetically. Results: Nucleotide sequence identities of the nucleoprotein gene and G-L intergenic region of the 26 RABVs were greater than 99.6 %. Phylogenetic analysis showed that all RABVs clustered with the vampire bat-related cattle RABV strains and that the RABVs were mainly distributed in southern Brazil. Conclusions: The findings of the present study suggested that a small population of rabid vampire bats carrying a single RABV strain produced a spatiotemporally restricted outbreak of cattle rabies in southern Brazil.
Keywords: Brazil; Cattle rabies; Molecular epidemiology; Vampire bat